2009
DOI: 10.1111/j.1540-8167.2008.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of PET/CT Fusion Imaging for Three‐Dimensional Myocardial Scar and Left Ventricular Anatomy during Ventricular Tachycardia Ablation

Abstract: Integration of 3D PET with Voltage Map for VT Ablation. Background: Image integration has the potential to display three-dimensional (3D) scar anatomy and facilitate substrate characterization for ventricular tachycardia (VT) ablation. However, the current generation of clinical mapping systems cannot display 3D left ventricle (LV) anatomy with embedded 3D scar reconstructions or allow display of border zone and high-resolution anatomic scar features. Objective: This study reports the first clinical experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…The reconstructed images were registered with voltage maps using precommercial CartoMERGE software. 10 Primary registration was performed with Landmark points and visual alignments as previously published. 10 Scar surface area and LV scar burden (scar surface area/total LV surface) were compared between the voltage map and 3D CE-CT reconstructions with the internal CartoMERGE measurement tools.…”
Section: Three-dimensional Ce-ct Image Reconstructionmentioning
confidence: 99%
“…The reconstructed images were registered with voltage maps using precommercial CartoMERGE software. 10 Primary registration was performed with Landmark points and visual alignments as previously published. 10 Scar surface area and LV scar burden (scar surface area/total LV surface) were compared between the voltage map and 3D CE-CT reconstructions with the internal CartoMERGE measurement tools.…”
Section: Three-dimensional Ce-ct Image Reconstructionmentioning
confidence: 99%
“…Recently, we showed that PET-derived myocardial scars can be successfully registered to display scars for VT ablations (6,7). Although PET has spatial resolution superior to SPECT (15,16), the availability of PET is limited because of higher costs.…”
Section: Rationale For Using Spect 3d Scar Modelsmentioning
confidence: 99%
“…3D SPECT scar surface models and voltage maps were compared using a 17-segment cardiac model (6). Segments were visually classified by an experienced cardiologist.…”
Section: Comparison Of 3d Spect Scar and Surface Models With Voltage mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that current imaging techniques do not take into consideration the triggering mechanisms and substrate modulators, such as sympathetic cardiac innervation (4)(5)(6)(7)(8)(9). The relationships between cardiac autonomic nervous system dysfunction, cardiomyopathy, and cardiac arrhythmias have been long established (10)(11)(12).…”
mentioning
confidence: 99%